(untitled) (Research, Society and Development, 2025)
Watermelon (Citrullus lanatus), belonging to the Cucurbitaceae family, is sensitive to water deficit during its development. As an alternative to mitigate this problem, hydrogel, a superabsorbent polymer capable of retaining water in the soil for longer periods, has been used. The objective of this study was to evaluate the effect of different doses of hydrogel on watermelon seedling production in styrofoam trays. The experiment was conducted between June and July 2025, in a screened nursery at the Federal Institute of Education, Science and Technology of the Triângulo Mineiro, Fazenda Sobradinho, Uberlândia (MG), Brazil. A completely randomized design was used with four treatments (0; 6.0; 10.0; and 14.0 g·kg⁻¹ of hydrogel), four replications, and 1.700 kg of substrate per tray with 128 cells. The hydrogel was previously diluted in 1 liter of water and mixed into the substrate. After 27 days, seedlings were evaluated for root and shoot length, fresh and dry mass of roots and shoots. Statistical analysis was performed using the Sisvar® software. Results indicated that hydrogel use caused significant differences in root dry matter, with higher doses reducing biomass accumulation. It is concluded that, although hydrogel increases water availability, excessive use may limit root development of watermelon seedlings.